Aneurysmal dilatation of left atrial appendage diagnosed by cross sectional echocardiography and surgically removed. Issue 1 (January 1985) - Lipkin, D; Colli, A; Somerville, J
Abstract : An isolated aneurysmal dilatation of the left atrial appendage was found in an 18 year old girl who presented with atrial fibrillation and an unusual cardiac shadow on routine chest radiographs. The diagnosis was made by cross sectional echocardiography. The giant appendage was excised to remove the risk of systemic embolism and the need for life long anticoagulation.